2022
DOI: 10.3389/fpls.2022.928229
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Wheat (Triticum aestivum L.) and Cotton (Gossypium hirsutum L.) to Nitrogen Deficiency in the Root Morpho-Physiological Characteristics and Potential MicroRNA-Mediated Mechanisms

Abstract: Understanding the mechanism of crop response to nitrogen (N) deficiency is very important for developing sustainable agriculture. In addition, it is unclear if the microRNA-mediated mechanism related to root growth complies with a common mechanism in monocots and dicots under N deficiency. Therefore, the root morpho-physiological characteristics and microRNA-mediated mechanisms were studied under N deficiency in wheat (Triticum aestivum L.) and cotton (Gossypium hirsutum L.). For both crops, shoot dry weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 98 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…MiRNA sequencing data revealed a significant increase in the abundance of miR171h (1.7-fold in shoots and 1.1-fold in roots) and miR396g (3.1-fold in roots), and a significant decrease in the abundance of miR167e/i-3p (-2.2-fold in roots) in salt-stressed DP seedlings. Previous research has shown that the upregulation of miR171 sRNAs enhances primary root elongation via manipulation of the quiescent center as well as the expression of Scarecrow-like 6-II (SCL6-II), SCL6-III, and SCL6-IV encoding genes in Arabidopsis , wheat, cotton, and rice cultivar Pokkali [ 7 , 50 , 51 ]. Similarly, an increase in the miR396 transcript abundance has also been identified to promote primary root growth in Arabidopsis and Medicago truncatula .…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA sequencing data revealed a significant increase in the abundance of miR171h (1.7-fold in shoots and 1.1-fold in roots) and miR396g (3.1-fold in roots), and a significant decrease in the abundance of miR167e/i-3p (-2.2-fold in roots) in salt-stressed DP seedlings. Previous research has shown that the upregulation of miR171 sRNAs enhances primary root elongation via manipulation of the quiescent center as well as the expression of Scarecrow-like 6-II (SCL6-II), SCL6-III, and SCL6-IV encoding genes in Arabidopsis , wheat, cotton, and rice cultivar Pokkali [ 7 , 50 , 51 ]. Similarly, an increase in the miR396 transcript abundance has also been identified to promote primary root growth in Arabidopsis and Medicago truncatula .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, implementing scienti cally and reasonably sound N fertilizer management methods is crucial for improving crop productivity and N use e ciency (Qiao et al, 2013;Khan et al, 2017;. Additionally, a comprehensive understanding of crop nutrient uptake mechanisms is essential for optimizing nutrient management and further advancing sustainable agriculture (Xue et al, 2022).…”
Section: Introductionmentioning
confidence: 99%